2021
DOI: 10.1039/d1ta03499e
|View full text |Cite
|
Sign up to set email alerts
|

Solid oxide proton conductors beyond perovskites

Abstract: Solid oxide proton conductors are crucially emerging as key materials for enabling hydrogen-based energy conversion, storage, and electrochemical technologies. Oxides crystallising in the ideal ABO3 perovskite structure, such as barium...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 288 publications
0
37
0
Order By: Relevance
“…Although, other classes of oxides (Ruddlesden–Popper, double perovskite, fergusonite/scheelite structures) also display proton transport, they concede to perovskite-structured phases in terms of achieving both high absolute levels and contributions of proton conductivity. 29,30 Due to this fact, BaCeO 3 , BaZrO 3 or their solid solutions (BaCeO 3 –BaZrO 3 or Ba(Ce,Zr)O 3 ) represent the most frequently-used basic oxides 31–36 for designing electrolyte membranes used in protonic ceramic fuel cells (PCFCs), protonic ceramic electrolysis cells (PCECs), protonic ceramic converters (PCCs), protonic ceramic pumps (PCPs), and protonic ceramic sensors (PCSs). As can be seen from Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Although, other classes of oxides (Ruddlesden–Popper, double perovskite, fergusonite/scheelite structures) also display proton transport, they concede to perovskite-structured phases in terms of achieving both high absolute levels and contributions of proton conductivity. 29,30 Due to this fact, BaCeO 3 , BaZrO 3 or their solid solutions (BaCeO 3 –BaZrO 3 or Ba(Ce,Zr)O 3 ) represent the most frequently-used basic oxides 31–36 for designing electrolyte membranes used in protonic ceramic fuel cells (PCFCs), protonic ceramic electrolysis cells (PCECs), protonic ceramic converters (PCCs), protonic ceramic pumps (PCPs), and protonic ceramic sensors (PCSs). As can be seen from Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that proton transport in oxides, occurring according to the Grotthuss mechanism, is characterized by activation energies of ~0.5 eV. These values are typical for many perovskites and related structures, the comparison of activation energies E a of proton conductivity for various structures is presented in [ 49 ]. It should be emphasized that proton transport in hexagonal perovskites with general formula Ba 5 M 3+ 2 Al 2 ZrO 13 is realized with lower activation energies.…”
Section: Resultsmentioning
confidence: 99%
“…124 Recently solid oxides with ABO3 perovskite structures became key substances for enhancing hydrogen storage properties. 126 It was shown that porous NiTiO3 and CoTiO3 nanorods can decrease the dehydrogenation temperature of MgH2 and provide faster hydrogen desorption (Tdes = 261.5•C and Tdes = 298•C for NiTiO3 and CoTiO3, respectively). 127 Other mixed oxides such as NiMoO4 and CoMoO4 nanorods similarly enhance the non-isothermal and the isothermal desorption performance of magnesium hydride.…”
Section: Small Inorganic/organic Moleculesmentioning
confidence: 99%